Correlação clínica entre a osteonecrose medicamentosa por bisfosfonato e os valores sorológicos do telopeptídeo carboxi-terminal do colágeno tipo I - Rodrigues, Maria Flávia Milagre (2018)
Some complementary tests have been recommended for the analysis of the action of bisphosphonates (BF) on bone tissue, in order to prevent the development of bisphosphonate-related osteonecrosis of the jaw (BRONJ). Considering the biochemical markers, carboxy-terminal telopeptide of type I collagen (CTX), is considered the most discussed examination to estimate the development of BRONJ. However, the literature is rather controversial regarding its real efficacy, showing divergent results when CTX was correlated with cases of BRONJ. The objective of this study was to evaluate the CTX of patients with BF, with or without BRONJ, in order to estimate their precision in the surgical planning. The CTX value of 20 patients with BF was investigated and compared with the presence or absence of BRONJ, administration form and duration of BF use. Two groups were created: Group 1: 12 patients with BRONJ, with G1A eight patients presenting the previous complication, and G1B four patients who developed BRONJ after a surgical procedure. Group 2 corresponded to eight patients without BRONJ. Although seven patients showed CTX values at high risk, there was no significant difference between the groups evaluated (p = 0.534). There was no positive linear correlation between the time of BF use and the CTX dosage (r = -0.154). Correlations between the route of administration and CTX values showed a weak negative result for intravenous use (r = -0.232) and, for oral use, strong positive correlation (r = 0.968). When the CTX initial values of four patients who used oral BF were compared with all 16 patients who used the drug intravenously, no significant statistical difference was observed (Student's t-test, p = 0.884). From the results obtained, the CTX examination is an important additional tool, but it is not exclusive in estimating the development of OMMBF and, especially in cancer patients, it should be considered allied to the systemic and local conditions of each case.